Representation of the Self and Other in Joe Biden's Democratic National Convention Speech - Ingrit Vianica; Trisnowati Tanto (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2021)
This paper discusses the analysis of positive self-presentation and negative other-presentation in Joe Biden’s speech in Democratic National Convention on 20 August 2020. This research utilizes van Dijk’s Critical Discourse Analysis (CDA), in which the main analysis is related to social power abuse and inequality in the social and political context. The main purpose of this research is to find out how language contributes to build both positive and negative representation in the speech. However, the research will only focus on the micro-level approach which consists of macrostructure, microstructure, and superstructure analyses. This research employs a qualitative descriptive method since it involves data interpretation in describing the representation. The result of the analysis shows that Biden as the Self has a positive representation; on the other hand, Trump as the Other has a negative representation. Both negative and positive representation are formed through various tools. Through this analysis, it is hoped that people can be more critical in absorbing the information given by political figures.